Effect of hyperacute administration (within 6 hours) of transdermal glyceryl trinitrate, a nitric oxide donor, on outcome after stroke - Woodhouse, Lisa J.; Scutt, Polly; Krishnan, Kailash; Berge, Eivind; Gommans, John; Ntaios, George; Wardlaw, Joanna M.; Sprigg, Nikola; Bath, Philip M.W. (American Heart Association, 2015)
Background and Purpose — Nitric oxide donors are candidate treatments for acute stroke, potentially through hemodynamic, reperfusion, and neuroprotectant effects, especially if given early. Although the large Efficacy of Nitric Oxide in Stroke (ENOS) trial of transdermal glyceryl trinitrate (GTN) was neutral, a prespecified subgroup suggested that GTN improved functional outcome if administered early after stroke onset.